Bays International Private Limited: Evolving Through Market Dynamics - Saad Jamal Farooqui; Jawaid Qureshi; Madiha Zeeshan; Kamran Ahmed Soomro (Institute of Business Management, 2020)
Bays International was incorporated in 1996. Over the years it faced numerous challenges including: high employee turnover (particulary saleforce), limited expansion capabilities, low penetration in semi-urban markets, high operating expenses like rentals, increasing duties (on luxury products), low cash-flows, low budgets for advertising and marketing as compared to competitors, less awareness amongst consumers, volatile consumer preferences (especially by millennial), weak brands' loyalties, counterfeits/fake products, smuggling and infiltration from grey channels, high number of foreign and local chains entering the market, price war especially with local chains, and uncertain political situation. Four interviews were conducted from management and two interviews from ex employees. Moreover, a lot of open access documents of the company were reviewed. Pertinent literature reveiew also revealed interesting insights about emerging consumer trends and cosmetic industry along with interviews of some marketing directors of leading global brands. The Bays leadership believes that key parameters are improving over time. The case covers how the company maneuvered itself since its inception and launched numerous other brands targeted towards different segments of the society, in order to steer towards growth in changing internal and external environment. The case is based on a scenario when there is yet another increase of taxes by the government in 2019 and presents troublesome situations to branding cum marketing strategy for the company to consider.